The effect of NaOCl dentin treatment on nanoleakage formation - Pioch, Thomas; Kobašlija, Sedin; Huseinbegović, Amina; Müller, Katja; Dörfer, Christof (Journal of biomedical materials research, 2001)
The term “nanoleakage” has been introduced to explain a penetration pathway within hybrid layers of the dentin-composite junction in the absence of gap formation. This phenomenon is argued in the literature to be a risk factor for the quality of the dentin bonding. NaOCl is a well-known agent used to remove collagen layers that are exposed after acid etching. The purpose of this study was to determine the influence of an NaOCl treatment of dentin to the formation of nanoleakage.
Gesehen am 24.02.2021
Die angegebene DOI funktioniert nicht